Effectiveness evaluation of aerial reconnaissance in battalion force protection operation using the constructive simulation. (April 2023) - Drozd, Jan; Rak, Luděk; Zahradníček, Pavel; Stodola, Petr; Hodický, Jan
The paper sets out the results of an experiment carried out using MASA SWORD simulator to verify the use of the unmanned aerial vehicle (UAV) reconnaissance model during battalion force protection activities. The authors focus particularly on the first phase of the battle—enemy approaching and early reconnaissance. The reconnaissance was planned using the UAV reconnaissance model which is part of the Tactical Decision Support System (TDSS). The aim of the experiment is to verify the possibilities of using the UAV reconnaissance model for battalion-size unit force protection and to compare this model with ordinarily used tactical procedures. The experiment proves the hypothesis defined in the introduction and quantifies some defined variables. Based on the result of the experiment, it is possible to state that UAV reconnaissance has significant impact on the effectiveness of the military mission. Moreover, the simulation environment opens a wide range of possibilities for future research including multiple simulations of the scenario, comparison of achieved results in dependence on the set conditions and variable settings, tailoring tactics for the scenario at hand, and so on.